Anwendung von System Dynamics zur Geschäftsmodellinnovation in einem B2B-Ökosystem - Ksouri-Gerwien, Christoph; Vorbohle, Christian (Digitale Plattformen und Ökosysteme im B2B-Bereich)

Supporting Business Model Decision-making in B2B Ecosystems: A Framework for Using System Dynamics - Ksouri-Gerwien, C.; Vorbohle, Christian (Proceedings of the 55th Hawaii International Conference on System Sciences (HICSS))

Architectural Management of OTF Computing Markets - Gottschalk, Sebastian; Vorbohle, Christian; Kundisch, Dennis; Engels, Gregor; Wünderlich, Nacy V. (On-The-Fly Computing -- Individualized IT-services in dynamic markets)

On-The-Fly Computing -- Individualized IT-services in dynamic markets - Haake, Claus-Jochen; Meyer auf der Heide, Friedhelm; Platzner, Marco; Wachsmuth, Henning; Wehrheim, Heike
In the proposal for our CRC in 2011, we formulated a vision of markets for IT services that describes an approach to the provision of such services that was novel at that time and, to a large extent, remains so today: „Our vision of on-the-fly computing is that of IT services individually and automatically configured and brought to execution from flexibly combinable services traded on markets. At the same time, we aim at organizing markets whose participants maintain a lively market of services through appropriate entrepreneurial actions.“ Over the last 12 years, we have developed methods and techniques to address problems critical to the convenient, efficient, and secure use of on-the-fly computing. Among other things, we have made the description of services more convenient by allowing natural language input, increased the quality of configured services through (natural language) interaction and more efficient configuration processes and analysis procedures, made the quality of (the products of) providers in the marketplace transparent through reputation systems, and increased the resource efficiency of execution through reconfigurable heterogeneous computing nodes and an integrated treatment of service description and configuration. We have also developed network infrastructures that have a high degree of adaptivity, scalability, efficiency, and reliability, and provide cryptographic guarantees of anonymity and security for market participants and their products and services. To demonstrate the pervasiveness of the OTF computing approach, we have implemented a proof-of-concept for OTF computing that can run typical scenarios of an OTF market. We illustrated the approach using a cutting-edge application scenario – automated machine learning (AutoML). Finally, we have been pushing our work for the perpetuation of On-The-Fly Computing beyond the SFB and sharing the expertise gained in the SFB in events with industry partners as well as transfer projects. This work required a broad spectrum of expertise. Computer scientists and economists with research interests such as computer networks and distributed algorithms, security and cryptography, software engineering and verification, configuration and machine learning, computer engineering and HPC, microeconomics and game theory, business informatics and management have successfully collaborated here.

Dear Guests, please pay for my license – Analyzing the heterogenous cost-pass-through of commercial and non-commercial rental suppliers in response to regulatory policies - Müller, Michelle; Neumann, Jürgen; Kundisch, Dennis (Proceedings of the 55th Hawaii International Conference on System Sciences (HICSS))

Exploring purposes of using taxonomies - Schoormann, T.; Möller, F.; Szopinski, Daniel (Tagungsband der 17. Internationalen Tagung Wirtschaftsinformatik 2022)

Situational Business Model Developer: A Tool-support for Situation-speciﬁc Business Model Development - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (Proceedings of the 17th International Conference on Wirtschaftsinformatik)
The development of business models is a challenging task that can be supported with software tools. Here, existing approaches and tools do not focus on the company’s situation in which the development takes place (e.g., ﬁnancial resources, product type). To tackle this challenge, we used design science research to develop a situation-speciﬁc business model development approach that contains three stages: First, existing knowledge in terms of tasks to do (e.g., analyze competitive advantage), and decisions to be made (e.g., social media marketing) are stored in repositories. Second, the knowledge is used to compose a development method based on the company’s situation. Third, the development method is enacted to develop a business model. This demonstration paper presents a tool-support called Situational Business Model Developer that supports all stages of our approach. We release the tool under open-source and evaluate it with a case study on developing business models for mobile apps.
Keywords: Business Model Development; Situational Method Engineering; Tool Support

Three Layers of Abstraction—A Conceptual Framework for Theorizing digital Multi-Sided Platforms - Poniatowski, Martin; Lüttenberg, Hedda; Beverungen, Daniel; Kundisch, Dennis (Information Systems and e-Business Management, Special Issue on Platform Business Models and Platform Strategies)

Model-driven Continuous Experimentation on Component-based Software Architectures - Gottschalk, Sebastian; Yigitbas, Enes; Engels, Gregor (Proceedings of the 18th International Conference on Software Architecture Companion)
To build successful software products, developers continuously have to discover what features the users really need. This discovery can be achieved with continuous experimentation, testing different software variants with distinct user groups, and deploying the superior variant for all users. However, existing approaches do not focus on explicit modeling of variants and experiments, which offers advantages such as traceability of decisions and combinability of experiments. Therefore, our vision is the provision of model-driven continuous experimentation, which provides the developer with a framework for structuring the experimentation process. For that, we introduce the overall concept, apply it to the experimentation on component-based software architectures and point out future research questions. In particular, we show the applicability by combining feature models for modeling the software variants, users, and experiments (i.e., model-driven) with MAPE-K for the adaptation (i.e., continuous experimentation) and implementing the concept based on the component-based Angular framework.
Keywords: continuous experimentation; model-driven; component-based software architectures; self-adaptation

Methoden zum Design digitaler Plattformen, Geschäftsmodelle und Service-Ökosysteme - Robra-Bissantz, Susanne; Lattemann, Christoph; Laue, Ralf; Leonhard-Pfleger, Raphaela; Wagner, Luisa; Gerundt, Oliver; Schlimbach, Ricarda; Baumann, Sabine; Vorbohle, Christian; Gottschalk, Sebastian; Kundisch, Dennis; Engels, Gregor; et al. (HMD Praxis der Wirtschaftsinformatik)

Overcoming Silos: A Review of Business Model Modeling Languages for Business Ecosystems - Vorbohle, Christian; Kundisch, Dennis (Proceedings of the 30th European Conference on Information Systems (ECIS))

Key Properties of Sustainable Business Ecosystem Relationships - Vorbohle, Christian; Kundisch, Dennis

Modeling Business Models: A cross-disciplinary Analysis of Business Model Modeling Languages and Directions for Future Research - Szopinski, Daniel; Massa, Lorenzo; John, Thomas; Kundisch, Dennis; Tucci, Christopher (Communications of the Association for Information Systems)

An update for taxonomy designers: Methodological guidance from information systems research - Kundisch, Dennis; Muntermann, J.; Oberländer, A. M.; Rau, D.; Röglinger, M.; Schoormann, T.; Szopinski, Daniel (Business & Information Systems Engineering)

Low-code experimentation on software products - Gottschalk, Sebastian; Bhat, Rakshit; Weidmann, Nils; Kirchhoff, Jonas; Engels, Gregor (Proceedings of the 25th International Conference on Model Driven Engineering Languages and Systems: Companion Proceedings)

Feeless Micropayments and Their Impact on Business Models - Klein, M.; Kundisch, Dennis; Stummer, C. (Handbuch Digitalisierung)

Continuous Situation-specific Development of Business Models: Knowledge Provision, Method Composition, Method Enactment - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (International Journal on Software and Systems Modeling (SoSyM))
The development of new business models is essential for startups to become successful, as well as for established companies to explore new business opportunities. However, developing such business models is a continuous challenging activity where different tasks need to be performed, and business decisions need to be made. Both have to fit the constantly changeable situation in which the business model is developed to reduce the risk of developing ineffective business models with low market penetration. Therefore, a method for developing situation-specific business models is needed. As a solution, we refine the concept of situational method engineering (SME) to business model development. SME, in turn, provides means to construct situation-specific development methods out of fragments from a method repository. We develop a concept for the continuous situation-specific development of business models based on design science. The approach uses the roles of a domain expert, a method engineer, and a business developer together with a repository with method fragments for developing business models and a repository with modeling artifacts for supporting the development. Both repositories are filled by utilizing the experience of domain experts. Out of these repositories, situation-specific development methods for developing business models can be continuously composed based on the changeable situation by the method engineer and enacted by the business developer. We implement it as an open-source tool and evaluate its applicability in an industrial case study of developing a business model for a local event platform. Our results show that situation awareness supports the continuous development of business models.
Keywords: Business Model Development; Situational Method Engineering; Situation-specific; Business Model Canvas; Continuous Development

Towards Situation-specific Software Support for Cross-organizational Design Thinking Processes - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (Proceedings of the 5th International Workshop on Software-intensive Business (IWSiB'22))
Due to the increasing influences of a VUCA world, design thinking workshops have been established as a standard technique to build solutions according to uncertain customer needs. Concerning the ongoing pandemic and rising development of solutions across organizations, more and more workshops were conducted online with software support. However, existing software tools insufficiently address the different workshop situations in terms of the process (i.e., fixed tasks to conduct), the place (e.g., static online whiteboards), and people (i.e., synchronous working of all stakeholders). Therefore, we propose a design science study to develop a situation-specific software support that can be configured with flexible development processes, different places, and task-related people. Based on practical experience in existing research projects, we derive the initial design requirements and map them to a set of design principles. Out of that, we design a concept with its implementation as a software tool and point out open challenges.
Keywords: design thinking; situation-specific; cross-organizational; software support

Moment or Movement – An Empirical Analysis of the Heterogeneous Impact of Media Attention on Charitable Crowdfunding Campaigns - Müller, Michelle; Seutter, Janina; Müller, Stefanie Jutta Marianne; Kundisch, Dennis (Proceedings of the 42nd International Conference on Information Systems (ICIS))

Extending Business Model Development Tools with Consolidated Expert Knowledge - Gottschalk, Sebastian; Kirchhoff, Jonas; Engels, Gregor (Business Modeling and Software Design)

Drei Strategien zur Etablierung digitaler Plattformen in der Industrie - Lüttenberg, Hedda; Beverungen, Daniel; Poniatowski, Martin; Kundisch, Dennis; Wünderlich, Nancy (Wirtschaftsinformatik & Management)

Von datenbasierter zu datengetriebener Geschäftsmodellentwicklung: Ein Überblick über Software-Tools und deren Datennutzung - Gottschalk, Sebastian; Yigitbas, Enes
Die kontinuierliche Weiterentwicklung des eigenen Geschäftsmodells ist für eine Organisation von entscheidender Bedeutung, um wettbewerbsfähig und somit nachhaltig erfolgreich zu bleiben. Während für die Entwicklung neuer Geschäftsmodelle häufig Workshops und einfache Software-Tools zur Visualisierung genutzt werden, wurden in der Forschung bereits erste Ansätze von datengetriebener Geschäftsmodellentwicklung (GME) vorgestellt. Diese Ansätze nutzen dabei Daten, Informationen oder auch Wissen aus internen und externen Unternehmensquellen, um den GME-Prozess zu unterstützen. Innerhalb dieses Beitrags zeigen wir einige Ansätze aus der aktuellen Literatur und analysieren wie ihre Datennutzung den GME-Prozess unterstützt. Weiterhin stellen wir mit dem BMDL Feature Modeler ein Tool vor, welches den GME-Prozess mit Expertenwissen unterstützt.

Situation-specific Business Model Development Methods for Mobile App Developers - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (Enterprise, Business-Process and Information Systems Modeling)
The development of effective business models is an essential task in highly competitive markets like mobile ecosystems. Existing development methods for these business models do not specifically focus that the development process profoundly depends on the situation (e.g., market size, regulations) of the mobile app developer. Here, a mismatch between method and situation can lead to poor resource management and longer development cycles. In software engineering, situational method engineering is used for software projects to configure a development method out of a method repository based on the project situation. Analogously, we support creating situation-specific business model development methods with a method base and new user roles. Here, the method engineer obtains the knowledge of the domain expert and stores it in the method base as elements, building blocks, and patterns. The expert knowledge is derived from a grey literature review on mobile development processes. After this, the method engineer constructs the development method based on the described situation of the business developer. We provide an open-source tool and evaluate it by constructing a local event platform's business model development method.
Keywords: Business Model Development; Situational Method Engineering; Mobile App; Business Model Development Tools

Situation-specific Development of Business Models for Services in Software Ecosystems - Gottschalk, Sebastian (Advanced Software Engineering. Doctorial Consortium)

Towards Visualizing and Simulating Business Models in Dynamic Platform Ecosystems - Vorbohle, Christian; Gottschalk, Sebastian (Proceedings of the 29th European Conference on Information Systems (ECIS))
Platform-based business models underlie the success of many of today’s largest, fastest-growing, and most disruptive companies. Despite the success of prominent examples, such as Uber and Airbnb, creating a profitable platform ecosystem presents a key challenge for many companies across all industries. Although research provides knowledge about platforms’ different value drivers (e.g., network effects), companies that seek to transform their current business model into a platform-based one lack an artifact to reduce knowledge boundaries, collaborate effectively, and cope with the complexities and dynamics of platform ecosystems. We address this challenge by developing two artifacts and combining research from variability modeling, business model dependencies, and system dynamics. This paper presents a design science research approach to develop the platform ecosystem modeling language and the platform ecosystem development tool that support researcher and practitioner by visualizing and simulating platform ecosystems.
Keywords: Platform Ecosystems; Platform Ecosystem Modeling Language; Platform Ecosystem Development Tool; Business Models; Design Science

Toward Understanding the Complexity of Business Models – A Taxonomy of Business Model Dependencies - Vorbohle, Christian; Szopinski, Daniel; Kundisch, Dennis (Proceedings of the 29th European Conference on Information Systems (ECIS))

Design Principles for a Crowd-Based Prototype Validation Platform - Gottschalk, Sebastian; Aziz, Muhammad Suffyan; Yigitbas, Enes; Engels, Gregor (Software Business - 12th International Conference, ICSOB 2021, Drammen, Norway, December 2-3, 2021, Proceedings)

Situation- and Domain-specific Composition and Enactment of Business Model Development Methods - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (Product-focused Software Process Improvement)
Developing effective business models is a complex process for a company where several tasks (e.g., conduct customer interviews) need to be accomplished, and decisions (e.g., advertisement as a revenue stream) must be made. Here, domain experts can guide the choices of tasks and decisions with their knowledge. Nevertheless, this knowledge needs to match the situation of the company (e.g., financial resources) and the application domain of the product/service (e.g., mobile app) to reduce the risk of developing ineffective business models with low market penetration. This is not covered by one-size-fits-all development methods without tailoring before the enaction. Therefore, we conduct a design science study to create a situation-specific development approach for business models. Based on situational method engineering and our previous work in storing knowledge of methods and models in distinct repositories, this paper shows the situation-specific composition and enaction of business model development methods. First, the method engineer composes the development method out of both repositories based on the situational context. Second, the business developer enacts the method and develops the business model. We implement the approach in a tool and evaluate it with a industrial case study on mobile apps.
Keywords: Business Model Development; Situational Method Engineering; Lean Development; Kanban Boards; Canvas Models

Transforming into a Platform Provider: Strategic Options for Industrial Smart Service Providers - Beverungen, Daniel; Kundisch, Dennis; Wünderlich, Nancy (Journal of Service Management)
Purpose The purpose of this paper is to identify strategic options and challenges that arise when an industrial firm moves from providing smart service toward providing a platform. Design/methodology/approach This conceptual study takes on a multidisciplinary research perspective that integrates concepts, theories and insights from service management and marketing, information systems and platform economics. Findings The paper outlines three platform types – smart data platform, smart product platform and matching platform – as strategic options for firms that wish to evolve from smart service providers to platform providers. Research limitations/implications Investigating smart service platforms calls for launching interdisciplinary research initiatives. Promising research avenues are outlined to span boundaries that separate different research disciplines today. Practical implications Managing a successful transition from providing smart service toward providing a platform requires making significant investments in IT, platform-related capabilities and skills, as well as implement new approaches toward relationship management and brand-building. Originality/value The findings described in this paper are valuable to researchers in multiple disciplines seeking to develop and to justify theory related to platforms in industrial scenarios.
Keywords: Smart service; Platform; Interdisciplinary research; Manufacturing company; Smart service provider; Platform economics; Information systems; Multi-sided markets; Business-to-business (B2B) markets

ProConAR: A Tool Support for Model-based AR Product Configuration - Gottschalk, Sebastian; Yigitbas, Enes; Schmidt, Eugen; Engels, Gregor (Human-Centered Software Engineering. HCSE 2020)
Mobile shopping apps have been using Augmented Reality (AR) in the last years to place their products in the environment of the customer. While this is possible with atomic 3D objects, there is is still a lack in the runtime conﬁguration of 3D object compositions based on user needs and environmental constraints. For this, we previously developed an approach for model-based AR-assisted product conﬁguration based on the concept of Dynamic Software Product Lines. In this demonstration paper, we present the corresponding tool support ProConAR in the form of a Product Modeler and a Product Conﬁgurator. While the Product Modeler is an Angular web app that splits products (e.g. table) up into atomic parts (e.g. tabletop, table legs, funnier) and saves it within a conﬁguration model, the Product Conﬁgurator is an Android client that uses the conﬁguration model to place diﬀerent product conﬁgurations within the environment of the customer. We show technical details of our ready to use tool-chain ProConAR by describing its implementation and usage as well as pointing out future research directions.
Keywords: Product Configuration; Augmented Reality; Model-based; Tool Support

Active Business Model Development Tools: Design Requirements - Szopinski, Daniel (Proceedings of the 15th International Conference on Design Science Research in Information Systems and Technology (DESRIST))

Exploring design principles for stimuli in business model development tools - Szopinski, Daniel (Proceedings of the 41st International Conference on Information Systems (ICIS))

Toss a Coin to your Host - How Guests End up Paying for the Cost of Regulatory Policies - Müller, Michelle; Neumann, Jürgen; Gutt, Dominik; Kundisch, Dennis (Proceedings of the 41th International Conference on Information Systems (ICIS))

Business Model Dependencies: Towards conceptualizing dependencies for extending modeling languages for business models - Vorbohle, Christian; Szopinski, Daniel; Kundisch, Dennis

Model-based Product Configuration in Augmented Reality Applications - Gottschalk, Sebastian; Yigitbas, Enes; Schmidt, Eugen; Engels, Gregor (Human-Centered Software Engineering. HCSE 2020)
Augmented Reality (AR) has recently found high attention in mobile shopping apps such as in domains like furniture or decoration. Here, the developers of the apps focus on the positioning of atomic 3D objects in the physical environment. With this focus, they neglect the conﬁguration of multi-faceted 3D object composition according to the user needs and environmental constraints. To tackle these challenges, we present a model-based approach to support AR-assisted product con-ﬁguration based on the concept of Dynamic Software Product Lines. Our approach splits products (e.g. table) into parts (e.g. tabletop, ta-ble legs, funnier) with their 3D objects and additional information (e.g. name, price). The possible products, which can be conﬁgured out of these parts, are stored in a feature model. At runtime, this feature model can be used to conﬁgure 3D object compositions out of the product parts and adapt to user needs and environmental constraints. The beneﬁts of this approach are demonstrated by a case study of conﬁguring modular kitchens with the help of a prototypical mobile-based implementation.
Keywords: Product Configuration; Augmented Reality; Runtime Adaptation; Dynamic Software Product Lines

Digitale mehrseitige Plattformen – Besser verstehen, wie digitale Plattformen funktionieren - Kundisch, Dennis

Software tools for business model innovation: Current state and future challenges - Szopinski, Daniel; Schoormann, T.; John, Thomas; Knackstedt, R.; Kundisch, Dennis (Electronic Markets)

Hypothesis-driven Adaptation of Business Models based on Product Line Engineering - Gottschalk, Sebastian; Rittmeier, Florian; Engels, Gregor (Proceedings of the 22nd IEEE International Conference on Business Informatics)
The continuous innovation of its business models is an important task for a company to stay competitive. During this process, the company has to validate various hypotheses about its business models by adapting to uncertain and changing customer needs effectively and efficiently. This adaptation, in turn, can be supported by the concept of Software Product Lines (SPLs). SPLs reduce the time to market by deriving products for customers with changing requirements using a common set of features, structured as a feature model. Analogously, we support the process of business model adaptation by applying the engineering process of SPLs to the structure of the Business Model Canvas (BMC). We call this concept a Business Model Decision Line (BMDL). The BMDL matches business domain knowledge in the form of a feature model with customer needs to derive hypotheses about the business model together with experiments for validation. Our approach is effective by providing a comprehensive overview of possible business model adaptations and efficient by reusing experiments for different hypotheses. We implement our approach in a tool and illustrate the usefulness with an example of developing business models for a mobile application.
Keywords: Business Model Decision Line; Business Model Adaptation; Hypothesis-driven Adaptation; Software Product Line; Feature Model

Model-based Hypothesis Engineering for Supporting Adaptation to Uncertain Customer Needs - Gottschalk, Sebastian; Yigitbas, Enes; Engels, Gregor (Business Modeling and Software Design)
To build successful products, the developers have to adapt their product features and business models to uncertain customer needs. This adaptation is part of the research discipline of Hypotheses Engineering (HE) where customer needs can be seen as hypotheses that need to be tested iteratively by conducting experiments together with the customer. So far, modeling support and associated traceability of this iterative process are missing. Both, in turn, are important to document the adaptation to the customer needs and identify experiments that provide most evidence to the customer needs. To target this issue, we introduce a model-based HE approach with a twofold contribution: First, we develop a modeling language that models hypotheses and experiments as interrelated hierarchies together with a mapping between them. While the hypotheses are labeled with a score level of their current evidence, the experiments are labeled with a score level of maximum evidence that can be achieved during conduction. Second, we provide an iterative process to determine experiments that offer the most evidence improvement to the modeled hypotheses. We illustrate the usefulness of the approach with an example of testing the business model of a mobile application.
Keywords: Hypothesis Engineering; Model-based; Customer Need Adaptation; Business Model; Product Features

Visualize different: Towards researching the fit between taxonomy visualizations and taxonomy tasks - Szopinski, Daniel; Schoormann, Thorsten; Kundisch, Dennis (Tagungsband der 15. Internationalen Tagung Wirtschaftsinformatik 2020 (WI))

Criteria as a prelude for guiding taxonomy evaluation - Szopinski, Daniel; Schoormann, Thorsten; Kundisch, Dennis (Proceedings of the 53rd Hawaii International Conference on System Sciences (HICSS))

A Case for a New IT Ecosystem: On-The-Fly Computing - Karl, Holger; Kundisch, Dennis; Meyer auf der Heide, Friedhelm; Wehrheim, Heike (Business & Information Systems Engineering)

Jumping, dumping, and pumping: Three mental principles for idea generation to activate software-based tools in business model innovation - Szopinski, Daniel (Proceedings of the 32nd Bled eConference)

Because your taxonomy is worth it: Towards a framework for taxonomy evaluation - Szopinski, Daniel; Schoormann, T.; Kundisch, Dennis (Proceedings of the 27th European Conference on Information Systems (ECIS))

Business Models of Store-Oriented Software Ecosystems: A Variability Modeling Approach - Gottschalk, Sebastian; Rittmeier, Florian; Engels, Gregor (Business Modeling and Software Design)
In the last years, store-oriented software ecosystems are gaining more and more attention from a business perspective. In these ecosystems, third-party developers upload extensions to a store which can be downloaded by end users. While the functional scope of such ecosystems is relatively similar, the underlying business models differ greatly in and between their different product domains (e.g. Mobile Phone, Smart TV). This variability, in turn, makes it challenging for store providers to find a business model that fits their own needs. To handle this variability, we introduce the Business Variability Model (BVM) for modeling business model decisions. The basis of these decisions is the analysis of 60 store-oriented software ecosystems in eight different product domains. We map their business model decisions to the Business Model Canvas, condense them to a variability model and discuss particular variants and their dependencies. Our work provides store providers a new approach for modeling business model decisions together with insights of existing business models. This, in turn, supports them in creating new and improving existing business models.
Keywords: Software Ecosystems; Business Models; Variabilities

Debiasing Vandalism Detection Models at Wikidata - Heindorf, Stefan; Scholten, Yan; Engels, Gregor; Potthast, Martin (WWW)

Activate software-based business model development tools: An exploratory study - Szopinski, Daniel (3rd Business Model Conference)

The long tail of taxonomy evaluation criteria: A structured overview - Szopinski, Daniel; Schoormann, T.; Kundisch, Dennis (Proceedings of the 14th International Conference on Design Science Research in Information Systems and Technology (DESRIST))

Can stimuli improve business model idea generation? Developing software-based tools for business model innovation - Szopinski, Daniel (Proceedings of the ACM Creativity & Cognition)
A business model describes the mechanisms whereby a firm creates, delivers, and captures value. Following the steadily growing interest in business model innovation, software tools have shown great potential in supporting business model development and innovation. Yet, understanding the cognitive processes involved in the generation of business model ideas is an aspect of software design-knowledge that has so far been neglected. To investigate whether providing stimuli – in this case, brainstorming questions – can enhance individual creativity in this context, we conduct an exploratory experiment with over 100 participants. Our study is the first to systematically investigate the process of idea generation using a software-based business model development tool with stimuli. Our preliminary findings have the potential to support the future development of business model development tools and to refine the research design used to evaluate such tools.
Keywords: Business model innovation; idea generation; cognitive stimuli; business model development tools; experiment; creativity support system

Squaring the circle: Business model teaching in large classroom settings - Szopinski, Daniel (Journal of Business Models)
Business model innovation is typically taught in small seminars at universities. Teaching this intrinsically task-oriented subject to a large number of students is a challenge. In this paper we address this challenge by proposing an experiential and interactive approach to teaching business models in a large classroom setting.
Keywords: Business model teaching; peer assessment; experiential learning